2004
DOI: 10.1002/cncr.20289
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the characteristics and survival rate of hepatocellular carcinoma from 1976 to 2000

Abstract: BACKGROUNDThe authors analyzed changes in the characteristics and survival rate of patients with hepatocellular carcinoma (HCC) in the past 25 years.METHODSTrends in clinical characteristics and survival rate of patients with HCC were evaluated retrospectively based on data from 1365 patients who were diagnosed, treated, and followed between 1976 and 2000.RESULTSBetween 1976–1995, the number of patients with smaller tumors, a less advanced tumor stage, and with a lower Child–Pugh class increased markedly. No d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 25 publications
4
34
0
Order By: Relevance
“…This is consistent with current literature reported in both Western and Asian studies 34, 35, 36. In our study, this aging effect was observed only in patients with CHB‐related HCC.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with current literature reported in both Western and Asian studies 34, 35, 36. In our study, this aging effect was observed only in patients with CHB‐related HCC.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with the male prevalence of hepatic tumors [1][2][3]18,[22][23][24]. Most HCC development in rodent models is directly or indirectly associated with components of the Ras regulated signaling pathway, such as C-myc, cyclin D1, epidermal growth factor and growth hormone [25][26][27].…”
Section: Discussionsupporting
confidence: 92%
“…Distribution of patients across stages within each system and associated survival rates were compared to determine the usefulness of each system. In addition, we evaluated the usefulness of the three staging systems dividing two periods: period 1976-1990 (n = 497) and 1991-2003 (n = 1,011) to see the difference in the usefulness of systems by periods, because early detection of HCC was not frequent during the former period and was common during the latter (14).…”
Section: Methodsmentioning
confidence: 99%